2008
DOI: 10.1111/j.1365-2648.2007.04504.x
|View full text |Cite
|
Sign up to set email alerts
|

Verbal abuse experienced by nursing students

Abstract: Education and healthcare providers should prepare students to manage negative verbal exchanges during nursing education, and policies and support networks relating to managing verbal abuse in clinical practice should be available to nursing students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
2
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 45 publications
9
79
2
1
Order By: Relevance
“…Student reports of verbal aggression in clinical settings range from 35−92%. [14,[27][28][29] In addition, the gap observed between verbal aggression and other categories of violence in the current study is similar to previous results. For example, Celebioglu et al [29] recently reported that verbal aggression rates were 91.6% according to student nurses in Turkey; however, physical-sexual harrassment rates were approximately 8% in this same population.…”
Section: Exposure To Violencesupporting
confidence: 82%
See 3 more Smart Citations
“…Student reports of verbal aggression in clinical settings range from 35−92%. [14,[27][28][29] In addition, the gap observed between verbal aggression and other categories of violence in the current study is similar to previous results. For example, Celebioglu et al [29] recently reported that verbal aggression rates were 91.6% according to student nurses in Turkey; however, physical-sexual harrassment rates were approximately 8% in this same population.…”
Section: Exposure To Violencesupporting
confidence: 82%
“…[18] Many studies report that healthcare staff, including students, is exposed to more violent behaviours from patients and relatives in psychiatric clinics. [14,41,[44][45][46] The current results confirm these findings, as student nurses' ranked psychiatric clinics as the least safe place for clinical practice. However, in a study investigating horizontal violence in the first professional year, McKenna et al [41] found lower rates of horizontal violence in psychiatric clinics compared to other clinics.…”
Section: Consequences Of Violencesupporting
confidence: 79%
See 2 more Smart Citations
“…Also it is quoted that nursing students have the highest risk of experiencing aggression because of inexperience, frequent ward changes and the challenge of meeting new environments [5] . Although The World Health Organizations, the International Council of Nurses, and Public Services International recognize the incidence of violent episodes as a major health priority, the number of nurses affected by this problem still continues to rise [7,13] .…”
mentioning
confidence: 99%